1999
DOI: 10.1016/s0009-9236(99)90081-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of dapsone toxicity in patients with inflammatory dermatoses: Activity of acetylation and hydroxylation of dapsone as risk factors

Abstract: These observations are consistent with what is known about the toxicity profile of dapsone metabolites and suggest that assessing N-acetylation and N-hydroxylation capacities can help to identify subjects at increased risk of a toxic response. This approach of assessing the phenotypic measures of drug-metabolizing activity to predict adverse reaction may also apply to other drugs with metabolic-based adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
1
38
0
2
Order By: Relevance
“…Production of dapsone hydroxylamine is thought to be responsible for the hematological toxicity (especially methemoglobinemia) of dapsone (Israili et al, 1973;Coleman et al, 1989;Gill et al, 1995). A recent study reported more severe adverse reactions (anemia or neurotoxicity) in individuals who were both slow acetylators and rapid hydroxylators (Bluhm et al, 1999), presumably because more dapsone is metabolized via the detrimental hydroxylamine pathway rather than by acetylation. Overall, it seems unlikely that knowledge of acetylator status will assist with dosing of this drug.…”
Section: A Acetyltransferasementioning
confidence: 99%
“…Production of dapsone hydroxylamine is thought to be responsible for the hematological toxicity (especially methemoglobinemia) of dapsone (Israili et al, 1973;Coleman et al, 1989;Gill et al, 1995). A recent study reported more severe adverse reactions (anemia or neurotoxicity) in individuals who were both slow acetylators and rapid hydroxylators (Bluhm et al, 1999), presumably because more dapsone is metabolized via the detrimental hydroxylamine pathway rather than by acetylation. Overall, it seems unlikely that knowledge of acetylator status will assist with dosing of this drug.…”
Section: A Acetyltransferasementioning
confidence: 99%
“…117 The most severe incidence of toxicity occurred in individuals with a slow acetylator phenotype who are rapid hydroxylators, which is consistent with the role each pathway has in the activation and detoxification of the drug. 118 While slow acetylators are at a greater risk of toxicity from sulphonamides and dapsone, other therapeutic agents exhibit increased incidence of adverse reactions in rapid acetylators. Amonafide is a novel arylamine that has previously been used in clinical trials for the treatment of various cancers.…”
Section: Nat and Drug Responsementioning
confidence: 99%
“…Initiation of this adverse effect could arise via the generation of a reactive metabolite, but proof of such an intermediate for nomifensine has not been reported, despite demonstration of nomifensine antibodies in patients Mueller-Eckhardt, 1985, 1986). Nomifensine is an aromatic amine, and compounds containing aromatic amines such as dapsone have been shown to be associated with blood and liver toxicities (Bluhm et al, 1999;Kalgutkar et al, 2005). Also, a methyl catechol metabolite of nomifensine was demonstrated in humans, suggesting the possible presence of a catechol intermediate metabolite that could be the precursor of an electrophilic ortho-quinone.…”
Section: Discussionmentioning
confidence: 99%